EVALUASI PENANGGULANGAN TERJADINYA HILANG LUMPUR PADA PEMBORAN SUMUR “FAZ-32” LAPANGAN “FAZ” - Farisah Asmarani; abdul hamid; listiana satyawati (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2017)
“FAZ-32” well drilling on “FAZ” field is a development well which aims to increase the absorption point in Tuban formation. The problem occurs in drilling operations at “FAZ-32” well on “FAZ” field are the mud loss. Mud loss which happens on “FAZ-32” well that is occurs when penetrating Ngrayong Formation and Tuban Formation. Afterwards of drilling the “FAZ-32” well, stretch drill holes 12-1/4 lost circulation occurred at a depth of 7150 ft. Then in the stretch 8-1/2 mud loss occurred at a depth of 7536 ft, 7560 ft and 7641 ft. The problems in drilling wells “FAZ-32”, firstly, what is the cause of lost circulation. Secondly, whether the countermeasure of mud loss are appropriate or not.The methodology used to evaluate response of mud loss are collecting data (data of mud, data drilling, and data pump), make the calculations (mud hydrostatics pressure during loss, formation pressure, formation fracture pressure, equivalen circulating density (ECD) and bottom hole circulation pressure (BHCP), comparing Ph, Pf, BHCP and Pfr to determine the cause of mud loss and evaluating countermeasure of mud loss that has been done in field.Handling mud loss problem at “FAZ-32” well on “FAZ” field is well applied in some loss zone and has reached the desired target depth (productive zone).